2020
DOI: 10.25047/j-remi.v1i4.2145
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Rekam Medis Elektronik di Tempat Pendaftaran Pasien Gawat Darurat dan Rawat Inap RSUD K.R.M.T Wongsonegoro Kota Semarang

Abstract: Each hospital is required to hold records or records of all services provided to patients called medical records. Increasing the effectiveness of recording medical data that is accurate, fast, can take advantage of current technological advances through the implementation of the Electronic Medical Record (EMR) system in hospitals. RSUD K.R.M.T Wongsonegoro is one of the hospitals that has implemented an electronic medical record (EMR) especially in the inpatient and emergency department registration units. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 0 publications
1
8
0
1
Order By: Relevance
“…Regarding the acceptance of electronic medical records based on aspects of interest and behavior (behavioral intention to use), most of them have described that this system has been well received in terms of the intensity and interest of users in the electronic medical record system. This is in line with research (Febrianti et al, 2020) based on the aspect of interest (behavioral intention to use) obtained, namely users of the EMR system really need the system currently in use, because it makes the work of officers easier and has been considered very relevant to support services. health registration officers at TPPGD and TPPRI intend to use EMR as long as it helps their work, registration officers at TPPGD and TPPRI plan to use EMR in the future and hope to continue to use RME in the future.…”
Section: System Consistency and Integrationsupporting
confidence: 79%
See 2 more Smart Citations
“…Regarding the acceptance of electronic medical records based on aspects of interest and behavior (behavioral intention to use), most of them have described that this system has been well received in terms of the intensity and interest of users in the electronic medical record system. This is in line with research (Febrianti et al, 2020) based on the aspect of interest (behavioral intention to use) obtained, namely users of the EMR system really need the system currently in use, because it makes the work of officers easier and has been considered very relevant to support services. health registration officers at TPPGD and TPPRI intend to use EMR as long as it helps their work, registration officers at TPPGD and TPPRI plan to use EMR in the future and hope to continue to use RME in the future.…”
Section: System Consistency and Integrationsupporting
confidence: 79%
“…Perceived ease of use describes a person's level of confidence that the use of information systems is easy and does not require hard effort from the wearer (Rahayu et al, 2017). Other researchers who were also conducted by (Febrianti et al, 2020) showed that the perceived ease of use aspect of users felt that it was easy to use the EMR's application and was able to make it easier to speed up the registration process at TPPGD and TPPRI.…”
Section: System Consistency and Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The economic benefits of implementing Electronic Medical Records include cost savings, cost efficiency, and cost-effectiveness. 14,16,17,19,20 The application of Electronic Medical Records can reduce the use of paper that is usually used in Conventional Medical Records. 14 Furthermore, the use of EMR is a reduction in the cost of services or maintenance that is not needed.…”
Section: Economic Benefitsmentioning
confidence: 99%
“…13 In implementing Electronic Medical Records in hospitals, there are still obstacles including power failure problems or network disruptions that can hinder data processing. 14 The use of Electronic Medical Records is expected to be able to increase and strengthen the benefits of medical records. Utilization of Electronic Medical Records, especially for the benefit of services to patients, including clinical and administrative services.…”
Section: Introductionmentioning
confidence: 99%